LIVER TREMATODE INFECTION - OPISTHORCHIASIS AND CLONORCHIASIS: ACTUAL PROBLEMS AND PRINCIPLES OF DIAGNOSIS IN MODERN CLINICAL PRACTICE (REVIEW OF LITERATURE) - O. A. Baykova; N. N. Nikolaeva; E. G. Grishchenko; L. V. Nikolaeva (Acta Biomedica Scientifica, 2016)
The article highlights the importance of the problem of endemic liver trematode infection (opisthorchiasis and clonorchiasis) and the principles of their diagnosis from the perspective of the clinician. Closely related pathogens (Opisthorchis felineus, Opisthorchis viverrini, Clonorchis sinensis) of these diseases are group 1 carcinogens, promoting the development of cholangiocarcinoma of the liver, gallstones, pancreatitis and gastroduodenitis. Specific and early diagnosis of opisthorchiasis in humans is crucial for an appropriate and timely treatment. The basic method of diagnostics in the world clinical practice is a detection of eggs in fecal samples. Once a fecal sample is available, the modified formalin-ether sedimentation technique, the modified thick Kato smear and with Kato - Katz are used. As a single examination does not necessarily provide diagnostic certainty, repeated examinations are necessary to improve diagnostic sensitivity. Immunoassay is considered as an addition to parasitological examination. The EL1SA shows the best performance among the serological tests. Molecular-genetic method (PCR and Loop mediated isothermal amplification (LAMP) is ranked as the most promising. Due to their high specificity, such molecular diagnostic tests are likely to play an increasingly significant role in anthelminthic drug efficacy evaluations, the rigorous monitoring of reinfection patterns, and to investigate changes in the endemic range of the liver flukes.